1980
DOI: 10.2307/1129563
|View full text |Cite
|
Sign up to set email alerts
|

The Adult-Child Dyad as a Problem-Solving System

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Wiley, Society for Research in Child Development are collaborating with JSTOR to digitize, preserve and extend access to Child Development This content downloaded from 144.32.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(32 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…Hence the children's competence levels alert the parents to how demanding their teaching strategies should be. Pellegrini et al further recommended the exploration of the sequence of parental teaching strategies, as parents found it necessary on occasion to switch from more demanding to less demanding strategies when the child encountered difficulty (see Wertsch et al 1980). In sum, the findings strongly support the Vygotsky model of parents teaching children through the zone of proximal development and the adjustment of parental teaching consistent with the competence level of their children.…”
Section: Collaborative Researchmentioning
confidence: 83%
“…Hence the children's competence levels alert the parents to how demanding their teaching strategies should be. Pellegrini et al further recommended the exploration of the sequence of parental teaching strategies, as parents found it necessary on occasion to switch from more demanding to less demanding strategies when the child encountered difficulty (see Wertsch et al 1980). In sum, the findings strongly support the Vygotsky model of parents teaching children through the zone of proximal development and the adjustment of parental teaching consistent with the competence level of their children.…”
Section: Collaborative Researchmentioning
confidence: 83%
“…Gutmann and Turnure's (1979) investigation of slightly older children (ages 2-3 and 4-5 years) further established that mothers appear to adapt their gestures to the developmental level of their child, as mothers of the 4-5 year olds used more, and more complex, gestures than did mothers of 2-3 year-olds. Similarly, Wertsch and colleagues (1980) found that mothers provided more verbal and gestural guidance (e.g., points, handling of pieces) to younger compared to older preschoolers during a puzzle-solving task. Thus, similar to the way that parents adapt their speech to young children, there is evidence that they also adapt and simplify their gestures based on children's age or ability level.…”
Section: Adaptation Of Gestures To Children's Age and Abilitymentioning
confidence: 85%
“…As reviewed above, there is evidence that parents’ gestures differ based on their child's age (Gutman & Turnure, 1979; Iverson et al, 1999) and perceived competence (Wertsch et al, 1980). However, to our knowledge, no studies have simultaneously examined how the characteristics and effectiveness of parents’ gestures vary by child age in an informal teaching-and-learning task.…”
Section: Current Studymentioning
confidence: 99%
“…By "environmental self-regulation", the learner adapts material means and local conditions of his or her learning environment (Zimmerman, 2000). Depending on the self-evaluation of his or her difficulties in solving the task, the learner mobilizes his or her social environment through communicative solicitations: either he or she regulates a partner's behaviour, by requesting help or a demonstration, in need, by searching for approval of his or her actions; or he or she initiates referential joint attention on the task with the partner (Bandura, 1997;Bruner, 1983;DeCooke & Brownell, 1999;Heckhausen, 1988;Nelson-Le-Gall et al, 1990;Pressley, 1995;Puustinen, 1998;Rogoff, 1990;Stipek et al, 1992;Szepkouski, Gauvain, & Carberry, 1994;Wertsch et al, 1980;Winnykamen, 1993;Wood & Wood, 1999;Zimmerman, 2000).…”
Section: Self-regulationmentioning
confidence: 99%
“…The shared responsibility in the dyad and the parental use of active coping behaviour towards the child have an impact on his or her involvement in self-regulated learning (Bynum & Brody, 2005;Bronson, 2001;Elbers, Maier, Hoerstra, & Hoogsteder, 1992;Gauvain & Rogoff, 1989;Moss, 1990;Vygotsky, 1978;Wertsch et al, 1980;Wood & Wood, 1999). Sinha and Kumari (2001) reported a high positive relationship between parental induction of self-regulation and a child's use of deep processing strategies, with the attribution of his or her success to controllable factors.…”
Section: Parents' Regulation and Child's Self-regulationmentioning
confidence: 99%